2020
DOI: 10.1007/978-3-030-39306-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching DevOps in Academia and Industry: Reflections and Vision

Abstract: This paper describes our experience of delivery educational programs in academia and in industry on DevOps, compare the two approaches and sum-up the lessons learnt. We also propose a vision to implement a shift in the Software Engineering Higher Education curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Work at the University of Luxemburg [12] seems closer to what we have done, given its practical focus, but it is still structured as a traditional university module that spans several weeks. As described in Section III-E, the DevOps Lab lasts a single week (or two, if we consider the code review sessions to be part of the learning process), which we have found to be just the right amount of time for our students to pick up the essentials of DevOps, and build a basic set of skills.…”
Section: Discussionmentioning
confidence: 97%
“…Work at the University of Luxemburg [12] seems closer to what we have done, given its practical focus, but it is still structured as a traditional university module that spans several weeks. As described in Section III-E, the DevOps Lab lasts a single week (or two, if we consider the code review sessions to be part of the learning process), which we have found to be just the right amount of time for our students to pick up the essentials of DevOps, and build a basic set of skills.…”
Section: Discussionmentioning
confidence: 97%
“…• In the fourth assignment, students link GitHub and Google Cloud Platform to enable automated build and deployment support, allowing new images to be created and deployed when changes are pushed to GitHub. This uses the parts used in the third assignment, as well as Google Cloud Source Repositories 13 and Google Cloud Build 14 . Details of each of these assignments, including how the various processes and artifacts mentioned above are used, follow.…”
Section: A Assignment Overviewmentioning
confidence: 99%
“…Krusche and Alperowitz [11] describe a project course where continuous integration and continuous delivery techniques are introduced and used in support of real-world projects, while Süß and Billingsley [12] instead focus on using continuous integration as a feedback mechanism for classes with a large number of students but limited teaching resources. Benni et al [13] present a graduate-level course that includes both software architecture and DevOps principles in the context of a realistic software project, while Bobrov et al [14], [15] discuss both a graduatelevel DevOps course and industry training. Kuusinen and Albertsen [16] focus on both the technical and cultural aspects of DevOps and continuous delivery as part of a two week course taught with industry.…”
Section: Related Workmentioning
confidence: 99%
“…We have been deeply involved in recent years in teaching both undergraduate and graduate students at the university, and junior/senior professional developers in industry. We have been also working often with management [46,5].…”
Section: Education In Devopsmentioning
confidence: 99%
“…However, until recently, not much attention was dedicated to integrating these principles into a distributed setting winning out properties such as easiness of deployment, a lightweight design and development phase, and minimal need for integration testing. The idea of Microservices [18,29] and Devops [3,5,46] stem out exactly from this widespread and recognized need.…”
mentioning
confidence: 99%